2020
DOI: 10.1016/j.copsyc.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Power’s mission: impact and the quest for goal achievement

Abstract: Power activates social influence goals and goals linked to power roles-Power elicits goal orientation, energizing people towards actions that help initiate and advance any salient aims and desires-Power facilitates goal related cognition-Powerholders' goal orientation can be beneficial for the performance of some tasks-However, power can trigger the neglect of secondary goals, social inattention and social objectification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…According to the situated focus theory of power ( Guinote, 2007a , 2007b , 2008 ), predispositions and social context, such as power roles and organizational norms, influence power holders’ priorities. These factors activate goals that ultimately affect power holders’ ethical conduct, in a situated ( Guinote & Chen, 2017 ; Guinote & Kim, 2020 ; Overbeck & Park, 2006 ) and nuanced ( Fleischmann et al, 2019 ) manner. For instance, the construal of power may emphasize having power over others or autonomy ( Lammers et al, 2009 ).…”
Section: Power Dominance and Dishonestymentioning
confidence: 99%
“…According to the situated focus theory of power ( Guinote, 2007a , 2007b , 2008 ), predispositions and social context, such as power roles and organizational norms, influence power holders’ priorities. These factors activate goals that ultimately affect power holders’ ethical conduct, in a situated ( Guinote & Chen, 2017 ; Guinote & Kim, 2020 ; Overbeck & Park, 2006 ) and nuanced ( Fleischmann et al, 2019 ) manner. For instance, the construal of power may emphasize having power over others or autonomy ( Lammers et al, 2009 ).…”
Section: Power Dominance and Dishonestymentioning
confidence: 99%
“…Cho and Keltner (2020) also found that those with power make faster decisions and act more promptly. Powerful individuals also engage in less deliberate decision-making processes (Fiske and Dépret, 1996) and have less foresight (consideration of "what happens if "; Guinote and Kim, 2020). Power works throughout the entire motivational process, from increasing goal setting, to early action, through to completion of the task (Guinote, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The learners master or expand the knowledge they have accumulated while solving the missions/quests they face. At the same time, instructors set learning goals through missions/quests [17]. The process of the learners solving the mission/quest is not a simple "repetition" of knowledge but a continuous expansion of knowledge.…”
Section: Gameful Experience and Motivationmentioning
confidence: 99%